2011
DOI: 10.1108/01425451111096695
|View full text |Cite
|
Sign up to set email alerts
|

“Modernising” away gender pay inequality? Some evidence from the local government sector on using job evaluation

Abstract: Purpose -This paper aims to focus on the use of job evaluation used as a mechanism to increase gender pay equality, drawing on data from the UK local government sector. Design/methodology/approach -Several research methods are used to collect data, including requesting information from local councils using the Freedom of Information Act, 2000, together with document analyses and interview data. Findings -While the paper questions the effectiveness of job evaluation in achieving pay equality objectives, within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
(23 reference statements)
0
9
0
1
Order By: Relevance
“…Pay equality issues in local authorities were at this stage well known across the UK, and steps to produce a single pay structure for manual and nonmanual staff were being sought through a single status agreement (Wright, 2011). In Scotland, 7 the 1999 Single Status Agreement, between local authorities and trade unions, included an obligation on councils to conduct an evaluation of all posts within their authorities and review their grading structures.…”
Section: Resultsmentioning
confidence: 99%
“…Pay equality issues in local authorities were at this stage well known across the UK, and steps to produce a single pay structure for manual and nonmanual staff were being sought through a single status agreement (Wright, 2011). In Scotland, 7 the 1999 Single Status Agreement, between local authorities and trade unions, included an obligation on councils to conduct an evaluation of all posts within their authorities and review their grading structures.…”
Section: Resultsmentioning
confidence: 99%
“…The article does not attempt to question Castle's assumption that there is a link between job evaluation and pay equality but notes some recent support for this claim (EHRC, 2009;Wright, 2011). Neither does the article attempt to determine whether trade unions have been able to extend job evaluation in the past but focuses on the question of whether there is anything preventing them now from extending the use of job evaluation to try and achieve equal pay.…”
Section: Methodsmentioning
confidence: 99%
“…A second type of claim arose from 'pay protection schemes' under which the pay of more highly paid workers was maintained at an artificially high level for a certain period after the implementation of the SSA, thereby perpetuating historical differences that favoured the male-dominated grades. A third legal strategy was to challenge the job evaluation schemes put in place at local level as part of the process of implementing the SSA, where it could be shown that they had a tendency to discriminate (see Wright, 2011;Gilbert, 2012). Finally, challenges were mounted to 'job enrichment schemes' under which job descriptions were redefined in an allegedly discriminatory manner.…”
Section: S Deakin Et Almentioning
confidence: 99%